Economic and social benefits of socially responsible actions towards employees in agribusiness enterprises = Ekonomiczne i społeczne korzyści działań społecznie odpowiedzialnych na rzecz pracowników w przedsiębiorstwach agrobiznesu - Matejun, Marek; Ratajczak, Marcin (Zielona Góra: Faculty of Economics and Management Press)
The aim of the paper is to identify the scope of socially responsible actions towards employees in agribusiness enterprises and to assess their impact on the level of economic and social benefits resulting from the use of the CSR concept in business practice. The survey research carried out on a sample of 325 companies from the SME sector conducting business in rural areas of the Mazowieckie Voivodeship served to meet the objective of the paper.
Keywords: społeczna odpowiedzialność biznesu; CSR na rzecz pracowników; obszary wiejskie; przedsiębiorstwa agrobiznesu; corporate social responsibility; CSR towards employees; rural areas; agribusiness enterprises